The Effect of Using Citric Acid and Lactic Acid Combination in Liquid and Encapsulated Forms as Feed Additive on Carcass Percentage and Internal Organ Weights of Broiler - Muhammad Halim Natsir (Faculty of Animal Science Universitas Brawijaya, 2008)
The purpose of this research were to find out effect of using citric acid and lactic acid combination in liquid and encapsulated forms on broiler carcass percentage and internal organ weights (liver, pancreas, lymph, bile). The material used for this research was 108 Cobb broiler chicks with average initial body weight of 44,00 Â± 3,37 g. The method used in this field experiment was Completly Randomized Design with 2 factors and 4 levels, and if there were significant influence it would be tested with Duncanâ€™s Multiple Range Test. The result showed that citric acid and lactic acid combination in either liquid or encapsulated form showed no significant effect (P>0,05) on carcass percentage and liver, pancreas and lymph weights of broiler but it significantly affect (P<0,01) bile weight. The addition of 0.4 % citric acid and lactic acid combination in either liquid or encapsulated form gave the best result on percentage carcass. The conclusion that the additions of different level of citric acid and lactic acid combination in encapsulated form on broiler feed only gave significant effect on lymph weight. Â Keywords: citric acid and lactic acid combination, liquid, encapsulated, carcass percentage, internal organ